The Chemical Composition and Antimicrobial Activity of the Leaf oil of Cupressus lusitanica from Monteverde, Costa Rica - Sara L Hassanzadeh; Jessika A Tuten; Bernhard Vogler; William N Setzer (Pharmacognosy Research, 2010)
The essential oils from the leaves of three different individuals of Cupressus lusitanica were obtained by hydrodistillation and analyzed by gas chromatography - mass spectrometry. A total of 49 compounds were identified in the leaf oils. The major components of C. lusitanica leaf oil were α-pinene (40%-82%), limonene (4%-18%), isobornyl acetate (up to 10%) and cis-muurola-4(14),5-diene (up to 7%). The essential oil was screened for antimicrobial activity, and it showed antibacterial activity against Bacillus cereus and antifungal activity against Aspergillus niger.
Keywords: 5-diene; Antimicrobial; cis -muurola-4(14); Composition; Cupressus lusitanica; Essential oil; Isobornyl acetate; Limonene; α-pinene